The Noncommutative Doplicher-Fredenhagen-Roberts-Amorim Space - Everton M.C. Abreu; Albert C.R. Mendes; Wilson Oliveira; Adriano O. Zangirolami (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
This work is an effort in order to compose a pedestrian review of the recently elaborated Doplicher, Fredenhagen, Roberts and Amorim (DFRA) noncommutative (NC) space which is a minimal extension of the DFR space. In this DRFA space, the object of noncommutativity (θ^{μν}) is a variable of the NC system and has a canonical conjugate momentum. Namely, for instance, in NC quantum mechanics we will show that θ^{ij} (i,j=1,2,3) is an operator in Hilbert space and we will explore the consequences of this so-called ''operationalization''. The DFRA formalism is constructed in an extended space-time with independent degrees of freedom associated with the object of noncommutativity θμν. We will study the symmetry properties of an extended x+θ space-time, given by the group P', which has the Poincaré group P as a subgroup. The Noether formalism adapted to such extended x+θ (D=4+6) space-time is depicted. A consistent algebra involving the enlarged set of canonical operators is described, which permits one to construct theories that are dynamically invariant under the action of the rotation group. In this framework it is also possible to give dynamics to the NC operator sector, resulting in new features. A consistent classical mechanics formulation is analyzed in such a way that, under quantization, it furnishes a NC quantum theory with interesting results. The Dirac formalism for constrained Hamiltonian systems is considered and the object of noncommutativity θ^{ij} plays a fundamental role as an independent quantity. Next, we explain the dynamical spacetime symmetries in NC relativistic theories by using the DFRA algebra. It is also explained about the generalized Dirac equation issue, that the fermionic field depends not only on the ordinary coordinates but on θ^{μν} as well. The dynamical symmetry content of such fermionic theory is discussed, and we show that its action is invariant under P'. In the last part of this work we analyze the complex scalar fields using this new framework. As said above, in a first quantized formalism, θ^{μν} and its canonical momentum πμν are seen as operators living in some Hilbert space. In a second quantized formalism perspective, we show an explicit form for the extended Poincaré generators and the same algebra is generated via generalized Heisenberg relations. We also consider a source term and construct the general solution for the complex scalar fields using the Green function technique.